OC-046 The ACPGBI/BSG Complex Colorectal Polyp Minimum Dataset: An Update. (17th August 2016) - Chattree, A; Barbour, J; Rutter, MD; ,
Abstract : Introduction: Variation in the assessment of large non-pedunculated colorectal polyps (LNPCPs) appears to lead to variable and suboptimal management outcomes. 1 Multidisciplinary discussion has been advocated to optimise management. Our ACPGBI/BSG evidence-based, expert consensus minimum dataset developed in 2014–15 has been felt to enhance LNPCP assessment and decision making. 2 We propose that further refinement will ensure increased robustness. Methods: A 14 person ACPGBI/BSG approved multidisciplinary panel reassessed the original minimum dataset using Delphi consensus methodology. A subcommittee tested the proforma dataset's applicability and usability for multidisciplinary discussion over 20 LNPCP cases. This process was intended to find any previously unidentified patient and polyp factors that may influence management. Proposed additional parameters were then subject to voting with >80% agreement required for consensus. The updated dataset was then assessed with a further 20 LNPCP cases. Results: 8 new parameters considered helpful for LNPCP assessment were identified. Whilst patient parameters such as symptoms, treatment preferences and comorbidity had previously been identified, it was agreed that establishing patient amenability to undergo treatment at another hospital was important and may potentially increase available therapeutic options. With regards to lesion characteristics, it was felt that specification of the 'SMSA scoring system' encouraged more comprehensive and standardised lesion assessment of the complexity of lesion endoscopic resectability. 2 Comprehensive photodocumentation was also considered necessary with parameters agreed relating to the capture of morphology and surface features and specific rectal imaging. Further piloting of the revised dataset identified no further required parameters (see figure). Conclusion: The development of an ACPGBI/BSG minimum dataset allows for comprehensive and standardised multidisciplinary LNPCP assessment. It forms part of a structured ACPGBI/BSG management framework for LNPCPs, also comprising guidelines and key performance indicators. In addition to facilitating multidisciplinary discussion, the dataset can also serve as an aide memoire to guide detailed endoscopic assessment. The updated consensus process ensures that all factors pertinent to decision making are included whilst applicability and usability are confirmed following further piloting. References: 1 Chattree A, Painter J, Silcock J, et al . Marked Variation in Endoscopic Mucosal Resection Outcomes within the UK Bowel Cancer Screening Programme. United European Gastroenterology Journal 2015;2 (Supp 1) 2 Rutter MD, Chattree A, Barbour J, et al . BSG/ACPGBI Guidelines for the management of large non pedunculated colorectal polyps. Gut 2015;0 :1–27 Disclosure of Interest: None Declared